DEVELOPMENT OF SIX-PHASE SYMMETRICAL COMPONENTS FILTERS FOR SELF-COMPENSATING POWER LINES - TURTURICA, Natalya (Journal of Engineering Science (Chişinău), 2022)
The paper deals with elaboration of hexaphase symmetrical components filters and their modeling to create microprocessor-assisted relay protection of self-compensating power lines. The theory is presented and the basic principial electrical schemes and mathematical models in the Matlab/Simulink of the filters of the hexaphase symmetric components are elaborated. The results of their simulation and testing at the computer are presented. The obtained results demonstrate the possibility of creating in the base on the elaborated filters of hexaphase symmetrical components the modern, efficient and highsensitivity microprocessor-assisted relay protection of self-compensating power lines. What reacted not to phase electrical values, but symmetrical components of them.